Analysis of Paint Material Requirements and Repair Costs for the KMP Balibo Ferry - Haslindah, Nurul; Sade, Juswan (Zona Laut Jurnal Inovasi Sains Dan Teknologi Kelautan, 2026)
The shipping industry is a crucial sector supporting maritime transportation in Indonesia, making ship maintenance and repair a vital requirement to ensure operational safety and efficiency. Painting is a crucial aspect of repair, protecting the ship's structure from corrosion while simultaneously reducing operational costs. This study aims to analyze the paint material requirements and painting costs for the KMP. Balibo ferry using the Just In Time (JIT) approach. This study provides a comprehensive overview of the calculation of material requirements and painting costs for the ship, while also offering a more effective inventory management strategy for the Indonesian shipbuilding industry. The primary data used include ship specifications, paint coating types, and material prices from official references. The analysis method is carried out by calculating the painting area, paint volume requirements, thinner, and material cost estimates based on the Dry Film Thickness, Solid Volume, Theoretical Spreading Rate, and paint loss factors. The results show that the total paint and thinner requirements can be estimated accurately, with a total cost of Rp 310.000.000. The implementation of the Just In Time (JIT) method results in more efficient material delivery planning, reduces potential waste, and accelerates the repair process.